STRATEGI MARKETING PUBLIC RELATIONS DALAM UPAYA MENINGKATKAN JAMAAH HAJI KHUSUS DAN UMROH - Abdulah, Fikrah; Mustiawan, Mustiawan; Setiawati, Titin (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2024)
This research analyzes the Marketing Public Relations (MPR) strategy by PT Fazary Wisata, a special Hajj and Umrah travel agency in Indonesia, in influencing prospective pilgrims to use their services. Indonesia, the country with the largest Muslim population in the world, has a high demand for Hajj and Umrah services, but the phenomenon of travel agency violations and fraud still occurs frequently. This research methodology uses a qualitative approach with a case study method. Data was collected through in-depth interviews, documentation, and literature study to gain in-depth understanding. The research results show that PT Fazary Wisata has successfully implemented the three main MPR strategies, namely Pull, Push, and Pass. The Pull strategy is carried out by building relationships through informative and interactive content on social media and their website. The Push strategy focuses on active promotion through advertising and exhibition activities to increase brand awareness and attract attention. Meanwhile, the Pass strategy uses the power of recommendations from satisfied congregants to build trust and loyalty. In conclusion, the combination of these three strategies has been effective in increasing the number of registrations of Hajj and Umrah pilgrims at PT. Fazary Wisata. Despite facing challenges in maintaining service quality and adapting to market changes, PT Fazary Wisata has great potential to continue to develop and strengthen its position in this competitive market. Keyword: Marketing Public Relations, Puss Pull Pass Strategy